2000
DOI: 10.1142/s0217979200001473
|View full text |Cite
|
Sign up to set email alerts
|

MÖSSBAUER STUDY OF In3+ AND Al3+ ADDITIVES IN MgMn FERRITES

Abstract: The effect of In 3+ and Al 3+ substitution in Mg-Mn ferrite has been studied from Mössbauer analyzes of Mg 0.9 Mn 0.1 MxFe 2−x O 4 (0 ≤ x ≤ 0.9) and Mg 0.9 Mn 0.1 Fe 2−y O 4 (0 ≤ y ≤ 0.5) ferrites. The internal magnetic field has been found to decrease at tetrahedral and octahedral sites when the concentration of In 3+ and Al 3+ ions is successively increased. A ferromagnetic relaxation followed by paramagnetic transition is observed for higher concentrations of In 3+ ions, it has been inferred that a larger c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In 3+ ions preferentially occupy the tetrahedral site [10], Al 3+ ions have a strong affinity to occupy the octahedral site [23] and Co 2+ ions preferentially occupy B site [24] but the increase in n B with increasing substitution of Co is attributed to the high exchange interaction energy and relatively higher orbital contribution of Co for the magnetic moment. In the case of increased In 3+ substitution, as the Fe 3+ (B)/ Fe 3+ (A) ratio increases which increases saturation magnetization and therefore n B increases, but with increasing Al 3+ ions, Fe 3+ (B)/Fe 3+ (A) ratio decreases and therefore the magneton number, n B , decreases.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3+ ions preferentially occupy the tetrahedral site [10], Al 3+ ions have a strong affinity to occupy the octahedral site [23] and Co 2+ ions preferentially occupy B site [24] but the increase in n B with increasing substitution of Co is attributed to the high exchange interaction energy and relatively higher orbital contribution of Co for the magnetic moment. In the case of increased In 3+ substitution, as the Fe 3+ (B)/ Fe 3+ (A) ratio increases which increases saturation magnetization and therefore n B increases, but with increasing Al 3+ ions, Fe 3+ (B)/Fe 3+ (A) ratio decreases and therefore the magneton number, n B , decreases.…”
Section: Article In Pressmentioning
confidence: 99%
“…It has been reported that in Mg-Mn ferrite if Fe ions are replaced by In [4,9,10], Al [1,4,10] and Co [11], the magnetic properties are modified. The citrate precursor method [12][13][14][15][16] ensures ease of preparation and control of composition, particle size, purity, homogeneity and uniform grain growth.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the gut microflora in the maturation of the mucosal immune barrier is regarded as predominant and expected to take place in the first years of life [44,45,46,47]. It is suspected that the increasing incidence of allergic diseases, seen among children of industrialized countries, is connected to their difficulty to establish a satisfactory protective endogenous gut flora, possibly as a consequence of a lowered consumption of foods produced by natural fermentation [39,44,45], along with a decreased contact with pathogens due to the increased hygienic conditions of modern housing [48][49][50][51]. These modified food habits along with modern life styles and changed environmental conditions have been cited as causes of stress that predispose humans to inflammatory, ulcerative, degenerative, auto-immune and infectious diseases [39].…”
Section: The Gastro-intestinal Ecosystem and The Well-beingmentioning
confidence: 99%
“…In this paper, magnetic and electrical properties of Mn 0.5 Zn 0.5 Fe 2 O 4 are discussed thoroughly. The performance of any ferrite is greatly influenced by its synthesizing technique [7][8][9][10][11][12][13]. The conventional ceramic method of preparation which involves solid state reaction between oxides at high temperatures is cumbersome, time consuming and does not always result in pure reproducible product.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional ceramic method of preparation which involves solid state reaction between oxides at high temperatures is cumbersome, time consuming and does not always result in pure reproducible product. Therefore, various non-conventional processing techniques [7][8][9], which are mainly solution techniques are reported. In the present work nonconventional preparation method, known as co-precipitation method, was used for preparation of Mn Zn ferrite.…”
Section: Introductionmentioning
confidence: 99%